Advanced Direct Injection Combustion Engine Technologies and Development : Gasoline And Gas Engines. - Zhao, H. (Woodhead Publishing, 2009)
Direct injection enables precise control of the fuel/air mixture so that engines can be tuned for improved power and fuel economy, but ongoing research challenges remain in improving the technology for commercial applications. As fuel prices escalate DI engines are expected to gain in popularity for automotive applications. This important book, in two volumes, reviews the science and technology of different types of DI combustion engines and their fuels. Volume 1 deals with direct injection gasoline and CNG engines, including history and essential principles, approaches to improved fuel economy, design, optimisation, optical techniques and their applications. Reviews key technologies for enhancing direct injection (DI) gasoline enginesExamines approaches to improved fuel economy and lower emissionsDiscusses DI compressed natural gas (CNG) engines and biofuels.